Income and Public Assistance Outcomes After Hurricane Maria: Evidence from Zip Code-Level Variation in Damage in Puerto Rico - Muñiz Sarriera,Estefanía (2025)
This research aims to study the relationship between population, income and public assistance outcomes in Puerto Rico after Hurricane Maria. This is done through an event style approach using zip code level data and a fixed effects estimation strategy. Precise hurricane damage are used to evaluate variations of the effects of damage types. A positive association is found between income per capita and hurricane damage, while a negative association is found between population and hurricane damage. The relationship between public assistance outcomes and hurricane damage yields mixed and inconclusive results. The results provide insights on post-hurricane processes.
Keywords: cyclones; income; public assistance; event study; Hurricane Maria; Puerto Rico